Building Resilience to Enhance Food and Nutrition Security, Incomes and Health in Northern Uganda (BRENU). Training Module 2: Enhancing smallholder household dietary diversity through kitchen gardens curriculum and facilitators’ guide - Owori, Moses; Ecii, Juliet; Opus, David; Akullo, Jacqueline; Kato, Fred; Nabuuma, Deborah; Ekesa, Beatrice (2022)
Background This training manual on the “Enhancing smallholder dietary diversity through kitchen gardens” has been developed by the Alliance of Bioversity International and CIAT, and used in the context of Building Resilience to Enhance Food and Nutrition Security, Incomes and Health in Northern Uganda (BRENU), an Action of the Development Initiative for Northern Uganda (DINU), a Government of Uganda programme implemented by International Institute of Tropical Agriculture (IITA) together with a consortium of five co-implementers namely: i) Volunteer Effort Development Concerns (VEDCO); ii) the Alliance of Bioversity International and CIAT (ABC); iii) Ernest Cook Ultra Sound Research and Education Institute (ECUREI); iv) Kilimo Trust and v) Rikolto International , supported by the European Union and supervised by the Office of the Prime Minister. As part of the consortium, ABC is responsible for conducting capacity building on nutrition for 2050 extension service providers representing 51,250 smallholder households. This training manual is part of a nutrition-sensitive package of formal training, informal technical assistance and mentoring services.